Promoting mental health and wellbeing as means to prevent disability: a review - Alsamiri, Yasir A.; Hussain, Malik A.; Alsamani, Omar A.; Al bulayhi, Abdulrahman A. (Frontiers in Public Health, 2024)
Background: Mental health is one of the key pillars of general welfare, and through its promotion, disability can be prevented. Objective: This research paper covers the field of literature that primarily addresses the increase of mental health and wellbeing aimed at preventing disability. Methodology: The analysis depends on secondary data that is acquired from different studies and reports to determine the link between mental health interventions and disability prevention. After screening, 50 articles eventually qualified for this narrative review. Results: The results indicate that prevention of mental health problems could reduce the risk of disability development by reducing underlying risk factors and, consequently, improving the quality of life. The study highlights the significance of early preventive interventions and support systems to curtail the onset of mental health disorders, which could later result in impairment. It does the same by advocating for multi-disciplinary approach that combines mental health promotion policies with existing disability prevention strategies to improve outcomes. Conclusion: The review points to mental health promotion as a preventative measure that can prevent disability and improve overall wellbeing. Through efforts to identify, prevent, and cure mental health problems, individuals can ensure optimal functioning and enjoy a better quality of life. Recommendation:This finding is indicative of a broader healthcare approach integrating mental health promotion that is aimed at diminishing the burden of disabilities and improving overall public health outcomes.